2020
DOI: 10.3390/ijms21072550
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Functionality of Plant Proteins from Low- to High-Solid Systems with Ligand and Co-Solute

Abstract: In the food industry, proteins are regarded as multifunctional systems whose bioactive hetero-polymeric properties are affected by physicochemical interactions with the surrounding components in formulations. Due to their nutritional value, plant proteins are increasingly considered by the new product developer to provide three-dimensional assemblies of required structure, texture, solubility and interfacial/bulk stability with physical, chemical or enzymatic treatment. This molecular flexibility allows them t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 160 publications
(205 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, HIU-treated samples showed LVE at a strain of<10 %, confirming that HIU treatment expanded the LVE of the MP solution. Earlier it was found that the G' and G'' values of the sonicated soybean isolate protein dispersion were lower than that of the unsonicated control, and the LVE was more expanded [48] . Also, in all samples, G' was dominant over G'' in LVE.…”
Section: Resultsmentioning
confidence: 93%
“…On the other hand, HIU-treated samples showed LVE at a strain of<10 %, confirming that HIU treatment expanded the LVE of the MP solution. Earlier it was found that the G' and G'' values of the sonicated soybean isolate protein dispersion were lower than that of the unsonicated control, and the LVE was more expanded [48] . Also, in all samples, G' was dominant over G'' in LVE.…”
Section: Resultsmentioning
confidence: 93%
“…Globular proteins, such as the ones found in lupin, create structures which characteristics are driven by the interaction of the protein with water molecules and governed by other additives [ 35 ]. The impact of TG and food grade additives on the functionality of LPI varied largely in the present study as shown in the 3-D images of reconstructured foam from X-ray tomography ( Figure 4 ; videos S1–S4; supplementary material ) and SEM ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Proteins solubility is typically reduced upon heating due to aggregation 61 . Protein deformation properties depend primarily on the number of disulfide bridges and ß‐sheet content 62 . For example, the high content of disulfide bridges in native 11S fraction of lupin protein isolates prevented molecular reconfigurations upon heat treatment 63 .…”
Section: Modification Methods Of Pulse Protein Ingredientsmentioning
confidence: 99%
“…61 Protein deformation properties depend primarily on the number of disulfide bridges and ß-sheet content. 62 For example, the high content of disulfide bridges in native 11S fraction of lupin protein isolates prevented molecular reconfigurations upon heat treatment. 63 The proteins with a greater proportion of ⊎-sheets were thermally more stable, need a higher temperature for gel formation, and produce stronger gels due to greater intermolecular interactions between them.…”
Section: Heat Treatmentmentioning
confidence: 99%